Multi-disciplinary Pastoral Living Labs for more sustainable territorial dynamics and development around collective rangelands - Frija, Aymen; Sghaier, Mongi; Rudiger, Udo; Idoudi, Zied; Oueslati-Zlaoui, Meriem (International Center for Agricultural Research in the Dry Areas, 2024)
This presentation focuses on the concept of "Pastoral Living Labs" (PLL) as a multidisciplinary approach to enhance sustainable management and development of collective rangelands. It discusses the significance of territorial intelligence and stakeholder dynamics in improving rangeland governance, the necessity for innovative research frameworks, and the practical challenges and achievements associated with implementing PLLs in Tunisia.